The readability of Malaysian english children story books - Adlina Ismail
Readability is defined as a text's level of difficulty to be comprehended by readers for a specific purpose. The readability of reading materials has been a great concern for many parties such as teachers, parents, and writers because they can be a source of emotional and cognitive enrichment. Locally published books are especially important in inculcating Mala sian identity and unity into the readers. However, a few public figures have expressed their worries over Malaysian books' quality for children. They mentioned that children books by local publishers are still at a low level and not suitable for children. Therefore, this study aims to study the readability of English children story books published by Malaysian publishers. Ten picture books and ten chapter books were collected as the samples of the study. The samples were collected using purposive sampling method. The study used Coh-Metrix TERA to analyze the readability of the samples according to indices which are aligned to the multilevel of discourse theory. Independent samples Mann-Whitney U test was conducted to compare the readability of picture books and chapter books to find the significant difference between the two children story book categories. It is found that the majority of picture book samples and only four chapter book samples are easy for children. Most of the difficulties in both picture books and chapter books are originated from the lack of cohesion particles such as very few connective words, signaling words, and repeated words. Meanwhile, results from the Mann- Whitney U test shows that picture books and chapter books differ significantly in terms of word concreteness, syntactic simplicity, and referential cohesion. Picture books are found to contain more concrete words, simple sentences, and repeated words compared to chapter books. This study concluded that the Malaysian children story books were not easy to be read by children. Therefore, it is suggested that serious attention should be given by Malaysian publishers to produce English story books for children that are not difficult to be read to cater to their cognitive and emotional needs.